2022
DOI: 10.3389/fcimb.2021.773665
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response 1 Suppresses Macrophage Phagocytosis by Inhibiting NRF2 Activation Through Upregulation of Autophagy During Pseudomonas aeruginosa Infection

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes life-threatening infections in cystic fibrosis patients and immunocompromised individuals. A tightly regulated immune response possessed by healthy individuals can effectively control P. aeruginosa infections, whereas the patients with dysregulated immune response are susceptible to this bacterial pathogen. Early growth response 1 (Egr-1) is a zinc-finger transcription factor involved in regulation of various cellular functions, including immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Consistent with our RNA-Seq and Ribo-Seq data, we found higher levels of Egr1 mRNA (Figure 2B) and protein in WT-infected cells at 60 min post WT Salmonella infection (Figure 2C-D). This upregulation was rapid but transient, consistent with previous reports 39, 40 . The abundance of mRNA peaked at 60 min and reduced to near baseline levels by 120 min.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our RNA-Seq and Ribo-Seq data, we found higher levels of Egr1 mRNA (Figure 2B) and protein in WT-infected cells at 60 min post WT Salmonella infection (Figure 2C-D). This upregulation was rapid but transient, consistent with previous reports 39, 40 . The abundance of mRNA peaked at 60 min and reduced to near baseline levels by 120 min.…”
Section: Resultssupporting
confidence: 92%
“…Recently, Pang et al. 59 have made an interesting observation that Egr1 suppresses macrophage phagocytosis by reducing the expression of P62, thus depriving Nrf2, the master regulator of anti-oxidative transcription, a key co-factor. 59 Because increased ROS production and/or impaired ROS clearance is a hallmark event in NAFLD pathogenesis, 60 targeting Egr1 could certainly help restore redox homoeostasis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we speculate that the reduced expression of IL6 and TNFα is due to distinct macrophage subsets in the lung tissue. Meanwhile, studies have shown that Nrf2 activation increased the phagocytic ability of THP-1 macrophages [ 55 ], and inhibition of NRF2 signaling suppresses the phagocytosis of P. aeruginosa by RAW264.7 macrophages [ 56 ]. Therefore, we speculate also that Nrf2-Exo may promote M2 macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%